Evaluating An Arabic Morphology Memorization Program: A CIPP Model Study at Mahad Hasan Bin Ali Samarinda - Andi Bangsawan Tolere; Misykat Malik Ibrahim; Rappe Rappe (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
lt;span lang=quot;EN-USquot;gt;Improving students’ comprehension in the Arabic language requires educators to design effective learning programs. However, implementation in the field still faces challenges such as low student interest and motivation, as well as suboptimal achievement of program objectives. This study aims to evaluate the Wazan Sharaf memorization program at Ma’had Hasan bin Ali Samarinda based on the four aspects of the CIPP model (Context, Input, Process, Product). The research employed a Mixed-Method Research (MMR) approach with first- and second-semester students as subjects. Data collection instruments included interview guidelines, observation, and tests, all validated by an external validator. The findings show that, in the context aspect, the program’s objectives and background align with the vision and mission of the Ma’had. In the input aspect, learning facilities are considered adequate, with the material sourced from lt;emgt;Mengenal Ilmu Sharaf Lebih Dekatlt;/emgt;, and instructors are deemed competent despite not graduating from Arabic Language Education programs. The process aspect reveals systematic learning implementation, though constrained by low memorization interest and limited time. The product aspect indicates improved student ability in understanding Wazan Sharaf. Recommendations include formalizing the program through official documentation, increasing learning time, utilizing technology, and strengthening material mastery.lt;/spangt; MARKER_1778183330